(untitled) (Research Papers, 2023)
The automatization of reporting processes in recent years is increasingly identified with the implementation and use of intelligent resource planning and management (ERP) systems in non-financial enterprises. Integrated business software is characterized by great functionality that provides rapidity and quality in solving accounting tasks, as well as in the process of financial planning, analysis, budgeting and control. Our research in the practice of non-financial enterprises show that most often the accountant that sign >signs the Annual Financial Statement (though not the only one) is the specialist who works, respectively administers an ERP system. This imposes >impose the need for BI competences.